2018
DOI: 10.22561/cvr.v29i1.3934
|View full text |Cite
|
Sign up to set email alerts
|

Deinstitutionalization of Activity Based Costing: Analysis From the New Institutional Sociology Perspective

Abstract: This study aimed at investigating, under the perspective of New Institutional Sociology, what factors led to the weakening and abandonment of Activity Based Costing in two companies. The study was based on a qualitative research method through case studies and evaluated the stages of ABC’ adoption, institutionalization stages and variables of deinstitutionalization. As a result, Beta reached the third stage and Gamma reached the second ABC adoption stage. The normative isomorphism encouraged by the recommendat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…The researchers deduced evidence from previous studies that the forces played little role in influencing companies to adopt the ABC system. Based on institutional isomorphism theory and content analysis, Aillon et al (2018) likewise supported the findings that mimetic pressures did not influence companies to adopt the ABC system. On the other hand, Alcouffe et al (2019) reported different results about ABC adoption where the effect of mimetic pressures was found to be statistically significant in their case.…”
Section: Empirical Literature Reviewsupporting
confidence: 53%
See 1 more Smart Citation
“…The researchers deduced evidence from previous studies that the forces played little role in influencing companies to adopt the ABC system. Based on institutional isomorphism theory and content analysis, Aillon et al (2018) likewise supported the findings that mimetic pressures did not influence companies to adopt the ABC system. On the other hand, Alcouffe et al (2019) reported different results about ABC adoption where the effect of mimetic pressures was found to be statistically significant in their case.…”
Section: Empirical Literature Reviewsupporting
confidence: 53%
“…The odds of contributions by mimetic and coercive pressures to level 3 ABC adoption were greater by 11% and 6.7%, respectively than the odds of contributions to level 1 ABC adoption while holding other levels (2,4,5) constant. At this level, in particular, the findings were consistent with the report by Alcouffe et al (2019) but disagreed with Aillon et al (2018). In an actual sense, copying the accounting practices of competitors and employing the strategies to meet the customers' and suppliers' demands explained the companies' move to level 3 of ABC implementation.…”
Section: Adoption Of Levelsupporting
confidence: 52%